(untitled) (FACE: Revista de la Facultad de Ciencias Económicas y Empresariales, 2022)
The general purpose of this study was to learn about the management and leadership styles of former rectors who excelled in a public university located in a peripheral region of Colombia. For this purpose, the proposal of Sánchez (2019) was taken into account, who pointed out that a leader may have an inclination either towards a task-oriented or a people-oriented management and leadership style. The study was qualitative in nature and approached with the analytical-synthetic method. On the other hand, the research was descriptive. Finally, with regard to the results, the former rectors made important contributions to the development of the university according to the interviewees and the documents reviewed.